Muscle-tendon mechanics and energetics during walking, running and jumping - Finni, T.; Cronin, N. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
In the human lower limb, muscles and tendon tend to interact in an efficient manner during common movements like walking, running and jumping. This pattern of interaction exploits the ability of muscles to produce forces efficiently at low shortening velocities, whilst tendons act as springs that help to store elastic energy during the contact phase, and return a large proportion of the energy in the pushoff phase. This pattern of muscletendon interaction can be disrupted in novel tasks or as a consequence of ageing or disease, resulting in a decrease in movement efficiency.